The Influence of Asset Inventory on Optimizing Fixed Assets at PT. Indomarco Prismatama - Limbeng, Ade Irma; Mahyudin, Mahyudin (Jurnal Akuntansi Hukum dan Edukasi, 2024)
This study aims to determine the effect of Asset Inventory on Fixed Asset Optimization at PT Indomarco Prismatama. The approach in this research is an associative / quantitative approach. The research was conducted at PT Indomarco Prismatama (Indomaret) which is located at JL Industri, No. 60, Tanjung Morawa B, Tanjung Morawa, Dagang Kerawan, Tj. Morawa, Deli Serdang Regency, North Sumatra 20362, Indonesia. Research started in February 2024 until completion. The population of this study were Indomaret employees who were in charge of recording assets and managing the assets of PT Indomarco Prismatama, 211 people and the number of samples in this study were 138 respondents. The data analysis technique uses simple regression. The results showed that Asset Inventory had a positive and significant effect on Fixed Asset Optimization at PT. Indomarco Prismatama Medan. Optimization of fixed assets at PT Indomarco Prismatama is determined or explained by the independent variable, namely asset inventory while the remaining 35.2% is influenced by other variables not examined in this study such as Maintenance and Maintenance, Employee Training and Competence and Asset Quality.